A Novel, Broad-Acting Peptide Inhibitor of Double-Stranded DNA Virus Gene Expression and Replication - Ruzsics, Zsolt; Hoffmann, Katja; Riedl, André; Krawczyk, Adalbert; Widera, Marek; Sertznig, Helene; Schipper, Leonie; Kapper-Falcone, Valeria; Debreczeny, Monika; Ernst, Wolfgang; Grabherr, Reingard; Hengel, Hartmut; et al. (Frontiers in Microbiology, 2020)
Viral infections are a global disease burden with only a limited number of antiviral agents available. Due to newly emerging viral pathogens and increasing occurrence of drug resistance, there is a continuous need for additional therapeutic options, preferably with extended target range. In the present study we describe a novel antiviral peptide with broad activity against several double-stranded DNA viruses. The 22-mer peptide TAT-I24 potently neutralized viruses such as herpes simplex viruses, adenovirus type 5, cytomegalovirus, vaccinia virus and simian virus 40 in cell culture models, while being less active against RNA viruses. The peptide TAT-I24 therefore represents a novel and promising drug candidate for use against double-stranded DNA viruses.